Download Presentation
## Polynomials

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -

**The Degree of axn**• If a does not equal 0, the degree of axn is n. The degree of a nonzero constant is 0. The constant 0 has no defined degree.**Definition of a Polynomial in x**• A polynomial in x is an algebraic expression of the form • anxn + an-1xn-1 + an-2xn-2 + … + a1n + a0 • where an, an-1, an-2, …, a1 and a0 are real numbers. an= 0, and n is a non-negative integer. The polynomial is of degree n, an is the leading coefficient, and a0 is the constant term.**Text Example**Perform the indicated operations and simplify: (-9x3 + 7x2 – 5x + 3) + (13x3 + 2x2 – 8x – 6) Solution (-9x3 + 7x2 – 5x + 3) + (13x3 + 2x2 – 8x – 6) = (-9x3 + 13x3) + (7x2 + 2x2) + (-5x – 8x) + (3 – 6) Group like terms. = 4x3 + 9x2 – (-13x) + (-3) Combine like terms. = 4x3 + 9x2 + 13x – 3**Multiplying Polynomials**The product of two monomials is obtained by using properties of exponents. For example, (-8x6)(5x3) = -8·5x6+3 = -40x9 Multiply coefficients and add exponents. Furthermore, we can use the distributive property to multiply a monomial and a polynomial that is not a monomial. For example, 3x4(2x3 – 7x + 3) = 3x4 · 2x3 – 3x4 · 7x + 3x4 · 3 = 6x7 – 21x5 + 9x4. monomial trinomial**Multiplying Polynomials when Neither is a Monomial**• Multiply each term of one polynomial by each term of the other polynomial. Then combine like terms.**Using the FOIL Method to Multiply Binomials**last first (ax + b)(cx + d) = ax · cx + ax · d + b · cx + b · d Product of First terms Product of Outside terms Product of Inside terms Product of Last terms inner outer**Text Example**Multiply: (3x + 4)(5x – 3).**Text Example**Multiply: (3x + 4)(5x – 3). Solution (3x + 4)(5x – 3) = 3x·5x + 3x(-3) + 4(5x) + 4(-3) = 15x2 – 9x + 20x – 12 = 15x2 + 11x – 12 Combine like terms. last first F O I L inner outer**The Product of the Sum and Difference of Two Terms**• The product of the sum and the difference of the same two terms is the square of the first term minus the square of the second term.**The Square of a Binomial Sum**• The square of a binomial sum is first term squared plus 2 times the product of the terms plus last term squared.**The Square of a Binomial Difference**• The square of a binomial difference is first term squared minus 2 times the product of the terms plus last term squared.**Special Products**Let A and B represent real numbers, variables, or algebraic expressions. Special ProductExample Sum and Difference of Two Terms (A + B)(A – B) = A2 – B2 (2x + 3)(2x – 3) = (2x) 2 – 32 = 4x2 – 9 Squaring a Binomial (A + B)2 = A2 + 2AB + B2 (y + 5) 2 = y2 + 2·y·5 + 52 = y2 + 10y + 25 (A – B)2 = A2 – 2AB + B2 (3x – 4) 2 = (3x)2 – 2·3x·4 + 42 = 9x2 – 24x + 16 Cubing a Binomial (A + B)3 = A3 + 3A2B + 3AB2 + B3 (x + 4)3 = x3 + 3·x2·4 + 3·x·42 + 43 = x3 + 12x2 + 48x + 64 (A – B)3 = A3 – 3A2B – 3AB2 + B3 (x – 2)3 = x3 – 3·x2·2 – 3·x·22 + 23 = x3 – 6x2 – 12x + 8**Text Example**Multiply: a. (x + 4y)(3x – 5y) b. (5x + 3y) 2 • Solution • We will perform the multiplication in part (a) using the FOIL method. We will multiply in part (b) using the formula for the square of a binomial, (A + B) 2. • a. (x + 4y)(3x – 5y) Multiply these binomials using the FOIL method. • = (x)(3x) + (x)(-5y) + (4y)(3x) + (4y)(-5y) • = 3x2 – 5xy + 12xy – 20y2 • = 3x2 + 7xy – 20y2Combine like terms. • (5 x + 3y) 2 = (5 x) 2 + 2(5 x)(3y) + (3y) 2 (A + B) 2 = A2 + 2AB + B2 • = 25x2 + 30xy + 9y2 F O I L**Example**• Multiply: (3x + 4)2. Solution: ( 3x + 4 )2=(3x)2 + (2)(3x) (4) + 42=9x2 + 24x + 16